Antioxidant Properties and Quantification of Phenolic and Flavonoid Compounds in Alpinia purpurata (Viell.) K. Schum Ethanol Extract - Djati, Muhammad Sasmito; Azerlyn, Defiona Rensia Naomi; Kusuma, Kavana Hafil; Rosyadah, Nuraini; Kamila, Fairuz Sarah; Annisa, Yuslinda; Christina, Yuyun Ika; Dwijayanti, Dinia Rizqi; Widodo, Nashi (Biotropika: Journal of Tropical Biology, 2025)
Phenolic and flavonoid compounds have been found to have positive benefits due to their antioxidant activity. Alpinia purpurata (Viell.) K. Schum, or lengkuas merah, is known to have aromatic rhizomes and is rich in active compounds such as flavonoids and phenolics. This research aimed to investigate the total phenolic and flavonoid content of A. purpurata ethanol extract and its antioxidant activity. A. purpurata was extracted using Microwave-Assisted Extraction (MAE) with 97% ethanol solvent. The ethanol extract of A. purpurata was then analyzed for the total phenolic and flavonoid content. The antioxidant activity and nitric oxide (NO) levels were determined by DPPH and NO scavenging assay, respectively. The results showed that A. purpurata ethanol extract had a high phenolic content (148.76 ± 1.03 mg GAE.g-1extract) but weak DPPH scavenging activity (IC50 of 219.06 ± 8.15 µg.mL-1), indicating that high phenolic content does not necessarily correlate with strong antioxidant properties. In contrast, the extract exhibited strong NO scavenging activity with an IC50 of 22.73 ± 7.57 µg.mL-1. Despite its high phenolic content, the weak DPPH activity indicates that total phenolic concentration alone is not always a reliable indicator of antioxidant strength. Further studies should include additional antioxidant assays to comprehensively evaluate the extract’s antioxidant potential.